THE INFLUENCE OF ENVIRONMENTAL CONSCIOUSNESS, ENVIRONMENTAL CONCERN, AND ENVIRONMENTAL KNOWLEDGE ON ATTITUDES AND THEIR IMPLICATIONS ON GREEN PURCHASE INTENTION OF ECO-FRIENDLY HOMES - Anggraini , Inneke; Imaningsih , Erna Sofriana; Wibowo, Mas Wahyu (International Journal of Social and Management Studies, 2023)
This study aims to determine and explain the influence of environmental consciousness, environmental concern, and environmental knowledge on green purchase intentions with attitude as a moderating variable. This type of research is a quantitative approach. The sample used was 160 visitors to the Bintaro Jaya housing at the marketing gallery office. The sampling technique used was purposive sampling. The data collection method used is an online questionnaire. Data processing using SmartPLS 3.0. The results of this research indicate that: 1) Environmental consciousness had a significant positive effect on attitudes, 2) Environmental concern had a positive and insignificant effect on attitudes, 3) Environmental knowledge is proven to had a significant positive effect on attitudes, 4) Attitude had a significant positive effect on the purchase intention of eco-friendly home products, 5) Environmental consciousness is proven to had a significant positive effect on the purchase intention of eco-friendly home products, 6) Environmental concern had a significant positive effect on the purchase intention eco-friendly home products, 7) Environmental knowledge had a positive and insignificant effect on the purchase intention eco-friendly home products, 8) Mediation effect attitude had a significant positive effect on environmental consciousness on purchase intention for eco-friendly home products, 9) Mediation effect attitude had a positive and insignificant effect on environmental concern on purchase intentions for eco-friendly home products, 10) Mediation effect attitude had a significant positive effect on environmental knowledge on purchase intention for eco-friendly home products.